Validity and reliability of the Secondary Traumatic Stress Scale‐Japanese version. Issue 4 (1st October 2021) - Kitano, Masato; Shoji, Kotaro; Nakaita, Ikumi; Sano, Shinya; Tachibana, Shoichi; Bride, Brian E.; Shigemura, Jun; Waki, Fumiko; Noguchi, Norihito; Koga, Minori; Toda, Hiroyuki; Yoshino, Aihide; et al.
Abstract: Aim: This study assessed the validity and reliability of the Secondary Traumatic Stress Scale‐Japanese Version. Methods: The original Secondary Traumatic Stress Scale was translated into Japanese, and Japanese items were back‐translated to English to confirm the accuracy of the translation. A total of 870 public health nurses from the Tohoku region in Japan completed the Secondary Traumatic Stress Scale‐Japanese Version. An exploratory factor analysis was conducted to identify the number of components. Moreover, 351 public health nurses from the Saitama prefecture in Japan also completed the scale. A confirmatory factor analysis was performed with the factor structure identified in the exploratory factor analysis. Results: The exploratory factor analysis identified two components: one associated with client‐related distress and the other with trauma‐related distress. The confirmatory factor analysis confirmed the two‐factor structure. The two‐factor structure model was better than the three‐factor model presented in the original validation study for the English version of the scale. The two‐factor model had good internal consistency for the overall product and the subscales. Pearson correlations showed that this model had good convergent validity against the Maslach Burnout Inventory, a psychological measure similar to the Secondary Traumatic Stress Scale. Finally, the two‐factor model had good discriminant validity against the Maslach Burnout Inventory. Conclusion: This study identified two components of the Secondary Traumatic Stress Scale‐Japanese Version that differ from the three components found in the original English version. The differences in the factor structure might indicate that the factor structure was culturally influenced. Abstract : We assessed the validity and reliability of the Secondary Traumatic Stress Scale‐Japanese Version. We identified two components of the Secondary Traumatic Stress Scale‐Japanese Version that differ from the three components found in the original English version. The differences in the factor structure might indicate that the factor structure was culturally influenced.